Women empowerment and dietary diversity among Tripura Tribal women in Bangladesh - Subarna Ghosh; Md. Mahbubur Rahman; Vhubaneshwar Tripura; Md. Zakaria Hider; Md. Shariful Islam; Sourov Ghosh Shuva; Md. Mojammel Haque Sakib; Mst. Rokshana Rabeya (PLoS ONE, 2026)
Background The empowerment of women is a global concern with significant implications both for individual well-being and societal progress. This study assessed the status of women’s empowerment and its relationship with dietary diversity among Tripura ethnic women in Khagrachari district, Bangladesh. Methods A cross-sectional survey was conducted with 230 randomly selected reproductive-aged women with a predesigned questionnaire. Significant relationships between socio-economic characteristics, women’s empowerment, women’s role in household food management, and Dietary Diversity Score (DDS) were examined by performing binary logistic regression analysis with the aid of Stata/MP 16.0 software. Results The study findings revealed that only 13.9% (32) of the Tripura tribal women are empowered, with a mean aggregated empowerment score of 0.51 ± 0.24. Dietary assessment showed that 25% of the respondents consumed fewer than five food groups, while 15% reported no intake of Animal Source Foods (ASFs). Furthermore, several factors appear to be associated with dietary diversity and ASFs consumption of women including education, (AOR = 3.80, 95% CI: 1.66–8.69; AOR = 3.04, 95% CI: 1.23–7.48), household structure, (AOR = 4.93, 95% CI: 2.24–10.87; AOR = 3.16, 95% CI: 1.32–7.57) and meal preparation roles (ASFs; AOR = 3.30, 95% CI: 1.12–9.75). Notably, empowered women had 10.53 times higher odds (AOR = 10.53, 95% CI: 1.40–79.10) of achieving greater DDS compared to their disempowered counterparts. Conclusion These findings highlight the importance of enhancing women’s empowerment, improving female education, and addressing household decision-making roles when designing nutrition interventions for tribal women.